High surface area carbon from polyacrylonitrile for high-performance electrochemical capacitive energy storage. Issue 47 (17th November 2016) - Gupta, Kishor; Liu, Tianyuan; Kavian, Reza; Chae, Han Gi; Ryu, Gyeong Hee; Lee, Zonghoon; Lee, Seung Woo; Kumar, Satish
Abstract : High surface area carbon with a surface area of 3550 m 2 g −1 is synthesized via a low-cost, scalable process from polyacrylonitrile. Abstract : High surface area carbon with a surface area of 3550 m 2 g −1 is synthesized via a low-cost, scalable process from polyacrylonitrile. The composite electrodes consisting of high surface area carbon and carbon nanotubes delivered a high capacitance of ∼174 F g −1 in symmetric configurations, and a high capacity of ∼150 mA h g −1 in asymmetric configurations against lithium metal with excellent rate-performance at practical mass loading and bulk densities.